Purification and Characterization of Antibacterial Protein from Pheretima javanica - Joko Waluyo; Bambang Sugiharto; Noor Cholies Zaini (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
This research aimed to examine and isolate antibakterial protein from three species of earthworms has antibacterial potencies. The research was conducted in several stages, namely: extraction earthworm by using three kinds of solvents; antibacterial activity test of earthworm extract by agar diffusion method; purification of antibacterial protein by using DEAE chromatography, filtration column chromatography, and Native-PAGE. The results showed that three species of earthworms contained antibacterial protein. The activity of antibacterial protein extract of Pheretima javanica in MOPS buffer was highestand the inhibition zone diameter were10.0-14.0 mm. Compared to the other solven, the of MOPS buffer most precise for the solvent of protein. The extract of Pheretima javanica with MOPS solvent was fractionated by using DEAE chromatography (anion exchanger) and produced three peaks of protein group. Among the peaks, last peak that need 0.380 M NaCl to eluate performed antibacterial activity. Further fractionation of the protein by using gel filtration chromatography produced two peaks and one of the peak has antibacterial activity. Further purification that carried out by cutting the active fraction of second protein peak by using Native-PAGE produced seven bands. A single protein of the sixth band from lowest band showed antibacterial activity.